GENERAL RISK FACTORS IN THE SYSTEM OF FORMING THE HEALTH OF THE POPULATION - Кудрявицька, Аліна; Карабач, Катерина; Шандра, В.В. (Modern engineering and innovative technologies, 2024)
The evolution of probabilistic methods of damage evaluation for human health has been caused by traditional approaches for environmental hazards evaluation restrictions and impossibility of direct cause-and-effect connections detection.